Kajian Pengerukan Waduk Sengguruh Kepanjen Kabupaten Malang - Endro Yuwono; Muhammad Sabaruddin (Jurnal Teknologi Terpadu, 2014)
Abstract sengguruh dam located between 07 ° 44'20 "- 08 ° 17'45" latitude and 112 ° 27'30 ° - 112 ° 57'55 ° E Longitude , Village Sengguruh, Kepanjen, Malang, East Java Province. The total volume of reservoir dam Sengguruh as much as 21.5 million  m3 ± 2.5 million m3 and ± 19 million m3 sediment trap . Sengguruh dam gets water supply from the Brantas River and Lesti River, both of them are components of the Brantas upstream water sheet with monthly average discharge 55.2 m3 / s and 2,065 mm of rainfall. Garbage in Sengguruh Dam reached 30 m3 / day and it is increased to 200 m3 / day during the rainy season. Average yearly total garbage and sediment reaching 5 million m3, meanwhile technical ability and sediment scavenge only about 300 thousand m3 / yr. Limitations of equipment and container land sediments become an obstacle. The rest, settle down and become disturbing waste dam. Hence it cause  production of hydroelectric power (hydropower) decreased from 29 MW / day to 18 MW / day. So that the to normalize function of reservoir need dredging, dredging effort in order to be effective required a proper plan by analyzing sediment, dredging equipment used, cost analysis and how much impact if the reservoir Sengguruh dredged to increase hydroelectric power production when viewed in terms of its economy. Keywords: Reservoir, sediment Abstrak Bendungan Sengguruh terletak diantara 07°44’20“ - 08°17’45“ LS dan 112°27’30° - 112°57’55° BT, Desa Sengguruh, Kepanjen, Kabupaten Malang, Propinsi Jawa Timur. Total volume tampungan Bendungan Sengguruh sebanyak 21,5 juta m3dengan rincian ±2,5 juta m3volume efektif dan ±19 juta m3tampungan volume sedimen. Bendungan Sengguruh mendapat pasokan air dari Sungai Brantas dan Sungai Lesti yang keduanya merupakan komponen hulu dari DAS Brantas dengan debit rata-rata bulanan 55,2 m3/s dan curah hujan 2,065 mm. Sampah di Bendungan Sengguruh mencapai 30 m3/hr dan sampah meningkat menjadi 200 m3/hr hari saat musim hujan. Rata-rata tiap tahun total sampah dan sedimen mencapai 5 juta m3sedangkan kemampuan teknis mengeruk sampah dan sedimen hanya sekitar 300 ribu m3/th. Keterbatasan peralatan dan lahan penampung sedimen menjadi penghambat. Selebihnya, sampah mengendap dan mengganggu bendungan. Dampaknya, produksi pembangkit listrik tenaga air (PLTA) menurun dari 29 MW/hr menjadi 18 MW/hr. Agar waduk bisa berfungsi normal perlu adanya pengerukan, agar upaya pengerukan berjalan efektif diperlukan rencana yang tepat dengan menganalisa sedimen, alat keruk yang dipakai, analisa biaya serta seberapa besar dampaknya bila waduk Sengguruh dikeruk untuk meningkatkan produksi listrik tenaga air bila ditinjau dari segi ekonominya.Kata Kunci : Waduk, sedimen